2010
DOI: 10.1021/nn1021346
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot DNA Bioconjugates: Attachment Chemistry Strongly Influences the Resulting Composite Architecture

Abstract: The unique properties provided by hybrid semiconductor quantum dot- (QD) bioconjugates continue to stimulate interest for many applications ranging from biosensing to energy harvesting. Understanding both the structure and function of these composite materials is an important component in their development. Here, we compare the architecture that results from using two common self-assembly chemistries to attach DNA to QDs. DNA modified to display either a terminal biotin or an oligohistidine peptidyl sequence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
170
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(180 citation statements)
references
References 60 publications
(139 reference statements)
8
170
0
Order By: Relevance
“…This strategy permits a moderate level of control over the number of biomolecules assembled per QD (conjugate valence) and their orientations; however, there are limitations associated with the heterogeneous attachment of the streptavidin to the underlying QD coating. 103 To date, the bioconjugate method that has provided the best overall control is self-assembly between polyhistidine-appended biomolecules and the ZnS shell of ligandcoated QDs ( Fig. 3vii; nanomolar dissociation constants), thereby providing excellent control over conjugate valence and orientation.…”
Section: Quantum Dot Materialsmentioning
confidence: 99%
“…This strategy permits a moderate level of control over the number of biomolecules assembled per QD (conjugate valence) and their orientations; however, there are limitations associated with the heterogeneous attachment of the streptavidin to the underlying QD coating. 103 To date, the bioconjugate method that has provided the best overall control is self-assembly between polyhistidine-appended biomolecules and the ZnS shell of ligandcoated QDs ( Fig. 3vii; nanomolar dissociation constants), thereby providing excellent control over conjugate valence and orientation.…”
Section: Quantum Dot Materialsmentioning
confidence: 99%
“…Conjugation of proteins with near neutral isoelectric points ( pIs) often reduces electrophoretic migration of QDs [89]. Contrarily, conjugation of DNA generally increases anodic migration, which is also affected by the length and number of DNA conjugated [76,79,90].…”
Section: Electrophoresismentioning
confidence: 99%
“…Loss of biomolecular activity is to be expected if the recognition site of the biomolecule is positioned in close proximity to the surface [30]. In a study of QD-DNA bioconjugates, Boeneman et al found that the attachment chemistry strongly influenced the orientation of DNA on a QD-poly(ethylene glycol) (PEG) surface [36]. His-tag-modified DNA attached directly to the QD surface resulted in a structure that, as predicted, extended out from the surface.…”
Section: Bioconjugationmentioning
confidence: 99%
“…However, given their NM nature, additional issues (also discussed in Section 6.2), such as the influence of the surface ligand on bioconjugation reactions and subsequent biomolecular interactions and how the attachment chemistry influences the NM stability and biomolecule orientation, should be considered for QDs [30,[33][34][35][36]515].…”
Section: Semiconductor Nanocrystalsmentioning
confidence: 99%